Sei sulla pagina 1di 6

# Squares that are sum of two squares

OR

## Solutions of Pythagoras theorems equation

OR

Solutions of x2 = y2 + z2

SANCHIT JAIN B.Tech. 5th Semester (Information Technology) National Institute of Technology Srinagar, India Email address me@sanchit.net

PREFACE

Ill lead you step-by-step to my final reckoning. If youll directly skip over to the results, this will seem too conspicuous & youll probably vote for me to be in the Top 10 fools in the world list. I know that this doesnt hold much significance (or maybe, none at all!) & youd probably be jeering at me when you read the title, but Im obsessed with numbers & I find this interesting, which might seem trivial to you. I love the patterns that exist among numbers. Although Ive also developed formulae of a lot higher significance, Ill not reveal them now. In case of any error or if theres anything Ive missed, please mail me at me@sanchit.net .

## Anyways, Ill begin:

Today, it struck my mind that (5)2 = (3)2 + (4)2, (13)2 = (5)2 + (12)2, (25)2 = (7)2 + (24)2. My brain, which rarely works, spotted the pattern 4 = 3x1 + 1 12 = 5x2 + 2 24 = 7x3 + 3 Let n assume values from 1,2,3. Accordingly, integers being multiplied with n can be represented by (2n + 1). The equation on the right side can be represented as (2n + 1)n + n = 2n(n + 1).

Thus, the squares following this pattern (eg. 5, 13, 25..their successive differences form an A.P. of common difference 4) are sum of (2n + 1)2 & (2n2 + 2n)2. So, they are (2n + 1)2 + (2n2 + 2n)2 = 4n4 + 8n3 + 8n2 + 4n +1 = (2n2 + 2n + 1)2
3

Squares of type[ k(2n2 + 2n + 1)]2 are always sum of squares [k(2n + 1)]2 & [k(2n2 + 2n)]2 . When k=1, n=1, we have (5)2 = (3)2 + (4)2. When k=1, n=2, we have (13)2 = (5)2 + (12)2. When k=3, n=1, we have (15)2 = (9)2 + (12)2. When k=4, n=1, we have (20)2 = (12)2 + (16)2.

This is just one of the types of squares that are sum of two other squares.

Now lets look at (8) + (15) = (17) . It doesnt satisfy the above result.
2 2 2

## Also, look at (4)2 + (3)2 = (5)2.

3 = 4 x (1)2 1 15 = 4 x (2)2-1

## Let n = 1,2,3,4 Clearly, (4n)2 + (4n2 - 1)2 = (4n2 + 1)2

At this point, I also vindicated that Im a fool. All of this seems so obvious now! All you need are two terms, one of which should be such that when the square of one is added to the seconds square, you get a squared term! But the first result would have been difficult to reckon had I thought about such terms instead of looking for patterns.
4

## Lets generalize all this

[k(a2xn2y + b2z)]2 is a square that is sum of squares [k(a2xn2y b2z)]2 & (2kaxbzny)2. When k = 1, x = 1, y = 1, z = 1, a = 1, b =1, (n2 + 1)2 = (n2 1)2 + (2n)2. When k = 1, x = 1, y = 1, z = 1, a = 2, b =1, (4n2 + 1)2 = (4n2 1)2 + (4n)2. When k = 1, x = 1, y = 1, z = 1, a = 3, b =2, (9n2 + 4)2 = (9n2 4)2 + (12n)2. When k = 1, x = 1, y = 1, z = 1, a = 4, b =3, (16n2 + 9)2 = (16n2 9)2 + (24n)2. When k = 1, x = 1, y = 1, z = 1, a = 3, b =4, (9n2 + 16)2 = (9n2 16)2 + (24n)2. When k = 1, x = 1, y = 1, z = 1, a = 1, b =2, (n2 + 4)2 = (n2 4)2 + (4n)2. An example of the above is (29)2 = (21)2 + (20)2 by putting k = 1, x = 1, y = 1, z = 1, a = 1, b = 2 & n = 5.

Also, [k(a2x + b2zn2y)]2 is a square that is sum of squares [k(a2x b2zn2y)]2 & (2kaxbzny)2.

The last 2 results can be used to find all squares that are sum of two squares. Actually n is required only if you want to make a formula to find squares that follow the same pattern.

NOTE : Based on the feedback I received, some people have been having problems understanding the results. Please note that these results are a consequence of (x2 + y2)2 = (x2 y2)2 + 4x2y2.